Assistance for Village Communities through the Nutrition Garden Program as an Effort to Reduce Stunting - Rahma, Tina Ayu; Muliawan, Muhammad Ramadhan; Rachman, Shifa Amelia; Syabrinah, Sulfah Sahratus; Sakinah, Sakinah; Falasifah, Nihlatul (Jurnal Soeropati, 2024)
This assistance activity focuses on efforts to reduce stunting through the nutrition garden program in Sumberdawesari Village, Grati District, Pasuruan Regency. The method used is Participatory Action Research with data collection techniques including interviews and Focus Group Discussions. The subjects of this community service activity include toddlers experiencing malnutrition or stunting, their parents, Posyandu cadres, farmer groups, and Family Welfare and Empowerment Organization. The results of the community service activities regarding the creation and management of the nutrition garden show that the program received positive appreciation from the community. The nutrition garden program has proven to have a significant impact on improving clean and healthy living behaviors, particularly in vegetable consumption habits, as well as providing economic benefits, food security, and enhancing community participation. Additional activities include providing supplementary food to support the growth of stunted toddlers. To support the sustainability and improvement of community nutrition, a nutrition garden group named Bhakti Bumi was established. Furthermore, the community was educated on nutritious food management through the presence of a nutrition expert from the Grati Pasuruan Health Center.